2020
DOI: 10.1177/0963689720917341
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aspects of Adipose-Derived Stromal Cell Senescence in a Long-Term Culture: A Potential Role of Inflammatory Pathways

Abstract: Long-term culture of mesenchymal stromal/stem cells in vitro leads to their senescence. It is very important to define the maximal passage to which the mesenchymal stromal/stem cells maintain their regenerative properties and can be used for cellular therapies and construction of neo-organs for clinical application. Adipose-derived stromal/stem cells were isolated from porcine adipose tissue. Immunophenotype, population doubling time, viability using bromodeoxyuridine assay, MTT assay, clonogencity, β-galactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The progressive death of adipocytes may lead to the release of DAMPs, which may subsequently induce a low-grade inflammatory response. On the other hand, the long-term culture of adipocyte progenitors such as preadipocytes can induce senescence of the growing cells, which function as mediators of inflammation associated with obesity [ 51 , 52 ]. It was reported that in addition to no longer undertaking their original function effectively, senescent cells can induce the secretion of proinflammatory factors in the tissue in which they reside [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progressive death of adipocytes may lead to the release of DAMPs, which may subsequently induce a low-grade inflammatory response. On the other hand, the long-term culture of adipocyte progenitors such as preadipocytes can induce senescence of the growing cells, which function as mediators of inflammation associated with obesity [ 51 , 52 ]. It was reported that in addition to no longer undertaking their original function effectively, senescent cells can induce the secretion of proinflammatory factors in the tissue in which they reside [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in addition to no longer undertaking their original function effectively, senescent cells can induce the secretion of proinflammatory factors in the tissue in which they reside [ 53 ]. Cellular senescence in adipocytes attenuates the physiological resolution of inflammation leading to a low-grade chronic inflammation, insulin resistance, type-2 diabetes, and companion senescence-associated secretory phenotype in the obese individual [ 51 , 52 , 53 ], indicating that these phenotypes are associated with impaired adipokine production. A detailed evaluation of senescence, cell death and DAMPs-mediated signaling pathway in PIP cells during LTAD would be of great value to further characterize this process in vitro and establish in parallel with the in vivo physiology.…”
Section: Discussionmentioning
confidence: 99%
“…All samples were measured in triplicate. Population doubling time of the cultured cells was determined as described previously [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The other issue is a danger of not obtaining necessary cell number, which is associated with cell senescence. Cells should be passaged maximally to 6th passage in order to maintain their regenerative properties, in some cases that time point may be not enough to obtain appropriate cell number, especially if the tissue source for cell isolation is limited [7,8]. In exchange for such restricted procedure we receive product which consists almost entirely of MSCs (>95%).…”
mentioning
confidence: 99%
“…However compared to heterogeneous population of SVF and BMMCs, pure MSCs have greater regenerative potential. Beside paracrine effect they can differentiate into many cell types, osteogenic, adipogenic and chondrogenic potential of MSC is also one of minimal criteria defining MSCs [7]. Like mentioned above, both methods have pros and cons, however in order to use "real" stem cell therapies more often in clinical practice, additional improvements in cell preparation, reducing the cost of procedure, have to be performed.…”
mentioning
confidence: 99%